Truncation or Deglycosylation of the Neuraminidase Stalk Enhances the Pathogenicity of the H5N1 Subtype Avian Influenza Virus in Mallard Ducks - Chen, Sujuan; Quan, Keji; Wang, Dandan; Du, Yinping; Qin, Tao; Peng, Daxin; Liu, Xiufan (Frontiers in Microbiology, 2020)
H5N1 subtype avian influenza virus (AIV) with a deletion of 20 amino acids at residues 49-68 in the stalk region of neuraminidase (NA) became a major epidemic virus. To determine the effect of truncation or deglycosylation of the NA stalk on virulence, we used site-directed mutagenesis to insert 20 amino acids in the short-stalk virus A/mallard/Huadong/S/2005 (rSNA-20) to recover the long-stalk virus (rSNA+). A series of short-stalk or deglycosylated-stalk viruses were also constructed basing on the long-stalk virus, and then the characteristics and pathogenicity of the resulting viruses were evaluated. The results showed that most of the short-stalk or deglycosylated-stalk viruses had smaller plaques, and increased heat and low pH stability, and a decreased neuraminidase activity when compared with the virus rSNA+. In a mallard ducks challenge study, most of the short-stalk or deglycosylated-stalk viruses showed increased pathological lesions and virus titers in the organ tissues and increased virus shedding in the oropharynx and cloaca when compared with the rSNA+ virus, while most of the short-stalk viruses, especially rSNA-20, showed higher pathogenicity than the deglycosylated-stalk virus. In addition, the short-stalk viruses showed a significantly upregulated expression of the immune-related factors in the lungs of the infected mallard ducks, including IFN-α, Mx1, and IL-8. The results suggested that NA stalk truncation or deglycosylation increases the pathogenicity of H5N1 subtype AIV in mallard ducks, which will provide a pre-warning for prevention and control of H5N1 subtype avian influenza in the waterfowl.